Effects of early dark energy on strong cluster lensing - Fedeli, Cosimo; Bartelmann, Matthias (Arxiv, 2017)
We use the semi-analytic method developed by Fedeli et al. for computing strong-lensing optical depths to study the statistics of gravitational arcs in four dark-energy cosmologies. Specifically, we focus on models with early dark energy and compare them to more conventional models. Merger trees are constructed for the cluster population because strong cluster lensing is amplified by factors of two to three during mergers. We find that the optical depth for gravitational arcs in the early dark-energy models is increased by up to a factor of about 3 compared to the other models because of the modified dynamics of cluster formation. In particular, the probability for gravitational arcs in high-redshift clusters is considerably increased, which may offer an explanation for the unexpectedly high lensing efficiency of distant clusters.